FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN HEALTH SEEKING BEHAVIOUR PADA GEJALA DEMAM DI MAHASISWA ANGKATAN TAHUN 2019 DAN 2020 FAKULTAS KEDOKTERAN UNIVERSITAS ISLAM AL-AZHAR - Moh. Reza Aulia Rahman; Artha Budi Susila Duarsa; Ayu Anulus; Aena Mardiah (Nusantara Hasana Journal, 2023)
Background: Health-seeking behavior is the behavior of an individual who is experiencing health problems to obtain treatment so that the health problems experienced are cured or reduced. A person's decision to seek treatment is very likely to be influenced by various factors such as individual, environmental, cultural factors, to perceptions of their health problems. The search for treatment needs to be carried out starting from underlying health problems such as fever symptoms to severe health problems. The health belief model is a concept commonly used to find out an individual's perception of whether or not they accept their health condition. The four main variables in the concept of the health belief model are perceived susceptibility, perceived severity, perceived benefits, and perceived barriers. Objective: To determine the factors associated with Health-seeking behavior in symptoms of fever in students of the Faculty of Medicine, Al-Azhar Islamic University, class of 2019 and 2020. Methods: Observational analytic quantitative study with a cross-sectional study design. The sampling technique was determined by random sampling method and the samples in this study were students of the Al-Azhar Islamic University Medical Faculty in 2019 and 2020. The data obtained was analyzed by the Chi Square test with a significance value (p ≤ 0.05). Results: Of the 120 research samples, 79.17% of students who sought treatment when suffering from fever symptoms had 43.4% perceived susceptibility, 30.8% perceived severity, 85.8% perceived benefits, and 14.5% perceived barriers. Obtained p value = 0.705 (p <0.05) for the relationship between perceived susceptibility and health-seeking behavior, p = 0.014 (p <0.05) for the relationship between perceived severity and health-seeking behavior, p = 0.952 (p <0, 05) for the relationship between perceived benefits and health-seeking behavior, and p = 0.000 (p <0.05) for the relationship between perceived barriers and health-seeking behavior. Conclusion: The results of the bivariate test show that perceived severity and perceived barriers in college students are significantly related to treatment-seeking behavior. Meanwhile, students' perceived susceptibility and perceived benefits statistically did not have a significant relationship to health-seeking behavior in students in the 2019 and 2020 batches of the Faculty of Medicine, Al-Azhar Islamic University.